ANALYSIS OF FOOD RETAIL EFFICIENCY IN SERBIA - Lukić, Radojko; Vojteski Kljenak, Dragana (Poslovna ekonomija, 2021)
As is well known, the problem of analyzing the efficiency of all companies, which means trading companies, is very topical, significant and complex. In the context of this, mathematical methods and models are increasingly being applied. With this in mind, this paper explores the effectiveness of food retailers in Serbia using AHP and DEA methods. Of all the observed optimization criteria (cost of goods sold, operating costs, gross margin and net profit), the most significant was the cost of goods sold. The most efficient food retailer in Serbia is Dlhaize Serbia. Mercator-S prem DEA analysis is inefficient. In order to improve the efficiency of food retailers in Serbia, it is necessary to apply the new business models (private brand, multichannel sales, organic food sales and others), the concepts of strategic management accounting and to strengthen the digitalization of business in the Western model.